Dame Ellen Terry correspondence and calling card - Terry, Ellen, Dame, 1847-1928.
ALS (1896 March 16; Chicago, Ill.) from Terry to Mrs. J.H. Hibbins relating to the death of actor Henry Howe written on a printed schedule for her fifth American tour (1895-1896) with Henry Irving; and a calling card for Terry (Mrs. C. Wardell) with note on verso.
British actress.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hibbins, J. H., -- Mrs. -- Correspondence; Howe, Henry, -- 1812-1896.; Irving, Henry, -- Sir, -- 1838-1905.; Theater -- Great Britain; Theater -- United States; Actresses